Evaluation of Agro-Morphological Traits of Some Introduced Okra [Abelmoschus esculentus (L) Moench] Varieties: Correlation, Variability and Heritability Studies - PK Dewi Hayati (Department of Crop Science, Faculty of Agriculture, Andalas University, 2020)
Okra is a functional vegetable with good nutritional content and medicinal benefits. The red okra cultivar has a lot of fruit in a single plant but have a short harvest period, thus the weight and size of the fruit are small. One of the techniques in the improvement of okra cultivar is performed by hybridization with the introduced okra varieties that have a longer harvest period. The objective of the research is to evaluate the crosses between red okra with the introduced okra varieties and to obtain plants from the crosses that have a longer fruit harvest period character. The research was conducted at the Research Station of the Faculty of Agriculture, Andalas University from Mei to October 2019. The materials used are the local red okra genotype, Ve-022, and B-291 introduced varieties as well as two of the crosses population of SOMB291 and SOMVe022. The whole plant is a red okra cultivar and the crosses are planted in a plot with a spacing of 40 x 50 cm. The performance of the crosses was analyzed using descriptive statistics. Results showed that the plant obtained with a longer harvest period of 8 days after anthesis as much as 19 and 12%, respectively in the population of SOMB291 and SOMVe022. The increase in crop life in plants from the somb291 and somve022 populations resulted in a plant that has a greater length, diameter, and weight than the red okra population. The increase in the harvest period results in a greater length, diameter, and weight of fruit.